2006
DOI: 10.1016/j.jsgi.2005.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the Transcriptional Coregulator FHL2 in Human Breast Cancer: A Clinicopathologic Study

Abstract: The specific expression in tumor tissue points to an important functional role of FHL2 in human breast cancer. Our survival data indicate that the expression of FHL2 in primary breast cancer is a potentially relevant prognostic factor. Further studies are warranted to elucidate whether analysis of FHL2 expression is suitable to predict response to antihormonal treatment with tamoxifen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
38
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 28 publications
1
38
0
Order By: Relevance
“…These data are in good agreement with and extend the recently published immunohistochemical investigation of FHL2 expression in breast cancer tissue. 40 Statistical evaluation performed by these authors showed further that overexpression of FHL2 in breast cancer is associated with poor survival prognosis. 23 Our findings together with these observations indicate that the FHL2 level in tumor cells reflects carcinogenic progression towards the malignant state.…”
Section: © 2 0 0 7 L a N D E S B I O S C I E N C E D O N O T D I S mentioning
confidence: 97%
See 3 more Smart Citations
“…These data are in good agreement with and extend the recently published immunohistochemical investigation of FHL2 expression in breast cancer tissue. 40 Statistical evaluation performed by these authors showed further that overexpression of FHL2 in breast cancer is associated with poor survival prognosis. 23 Our findings together with these observations indicate that the FHL2 level in tumor cells reflects carcinogenic progression towards the malignant state.…”
Section: © 2 0 0 7 L a N D E S B I O S C I E N C E D O N O T D I S mentioning
confidence: 97%
“…40 Statistical evaluation performed by these authors showed further that overexpression of FHL2 in breast cancer is associated with poor survival prognosis. 23 Our findings together with these observations indicate that the FHL2 level in tumor cells reflects carcinogenic progression towards the malignant state. Nevertheless, little is known about the function of FHL2 in mammary tumors and breast cancer cells.…”
Section: © 2 0 0 7 L a N D E S B I O S C I E N C E D O N O T D I S mentioning
confidence: 97%
See 2 more Smart Citations
“…[12][13][14][15] A number of studies from our laboratory and other groups provide evidence that FHL2 is involved in cancer progression. [16][17][18][19][20][21] Elevated expression of FHL2 and interaction with focal adhesion kinase (FAK) was found in human ovarian cancers, indicating a role of FHL2 and FAK complex during ovarian tumour progression. 17 We showed recently that activation of nuclear FHL2 signalling is linked to an aggressive biology and recurrence of prostate cancer.…”
mentioning
confidence: 99%